Tofacitinib Ameliorates Lupus Through Suppression of T Cell Activation Mediated by TGF-Beta Type I Receptor - Yan, Qing; Chen, Weiwei; Song, Hua; Long, Xianming; Zhang, Zhuoya; Tang, Xiaojun; Chen, Hongwei; Lin, He; Sun, Lingyun (Frontiers in Immunology, 2021)
Autoreactive T cells play a crucial role in the pathogenesis of systemic lupus erythematosus (SLE). TGF-β type I receptor (TGFβRI) is pivotal in determining T cell activation. Here, we showed that TGFβRI expression in naïve CD4+ T cells was decreased in SLE patients, especially in those with high disease activity. Moreover, IL-6 was found to downregulate TGFβRI expression through JAK/STAT3 pathway in SLE patients. In vitro, the JAK inhibitor tofacitinib inhibited SLE T cell activating by upregulating TGFβRI expression in a dose-dependent manner. In MRL/lpr mice, tofacitinib treatment ameliorated the clinical indicators and lupus nephritis, as evidenced by reduced serum anti-dsDNA antibody levels, decreased proteinuria, and lower renal histopathological score. Consistently, tofacitinib enhanced TGFβRI expression and inhibited T cell activation in vivo. Thus, our results have indicated that tofacitinib can suppress T cell activation by upregulating TGFβRI expression, which provides a possible molecular mechanism underlying clinical efficacy of tofacitinib in treating SLE patients.